2024
DOI: 10.7554/elife.88936
|View full text |Cite
|
Sign up to set email alerts
|

Detection of new pioneer transcription factors as cell-type-specific nucleosome binders

Abstract: Wrapping of DNA into nucleosomes restricts DNA accessibility and the recognition of binding motifs by transcription factors. A certain class of transcription factors, so-called pioneer transcription factors, can specifically recognize their binding sites on nucleosomal DNA, initiate local chromatin opening and facilitate the binding of co-factors in a cell-type-specific manner. For the vast majority of human pioneer transcription factors, the locations of their binding sites, mechanisms of binding and regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…As pTFs are characterized by their ability to bind nucleosomal DNA, we reasoned that their binding might be particularly sensitive to nucleosome composition. We thus quantified the number of pTFs that were enriched in the up vs downregulated motifs, using a classification of pTFs based on 57,58 (see Methods). We found that 87 out of the 376 up-TFs (23.1%) but only 7 out of the 97 (7.2%) down-TFs after 4 h of IAA treatment were known pTFs (Figure S5E).…”
Section: Srcap Depletion Unleashes Transcription Factor Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…As pTFs are characterized by their ability to bind nucleosomal DNA, we reasoned that their binding might be particularly sensitive to nucleosome composition. We thus quantified the number of pTFs that were enriched in the up vs downregulated motifs, using a classification of pTFs based on 57,58 (see Methods). We found that 87 out of the 376 up-TFs (23.1%) but only 7 out of the 97 (7.2%) down-TFs after 4 h of IAA treatment were known pTFs (Figure S5E).…”
Section: Srcap Depletion Unleashes Transcription Factor Bindingmentioning
confidence: 99%
“…The list of pioneer transcription factors (pTFs) (Table S5) was compiled from the list published by Lemma et al 57 in their supplementary Table 4 and Peng et al 58 in their supplementary Table 5 and 6.…”
Section: Tobias Analysismentioning
confidence: 99%